Determinant Factors of the Chrysanthemum Consumers’ Willingness to Pay: Case of Pasopati Cultivar - Puspita Dewi Hidayaningtyas; Irham Irham; Arini Wahyu Utami (Agro Ekonomi, 2021)
This study aims to: (1) determine the characteristics of chrysanthemum consumers in three cities in Java, namely Yogyakarta, Semarang and Surakarta, (2) compare the willingness to pay (WTP) of chrysanthemum consumers, especially Pasopati cultivar in the three cities, (3) analyze the determinant factors of the chrysanthemum consumers’ WTP. There is a total of 120 respondents who participated in this study, i.e., 40 in each city selected with accidental sampling. The consumers’ WTP was assessed using contingent valuation method, and its determinant factors was analyzed using multiple regression. The results showed that the majority of chrysanthemum consumers in the three cities were 17-25 years old, were female, held a bachelor degree, owned a job, were single and had no dependent. The value of wilingness to pay from the three cities shows higher results than the market price of IDR 30,000. The highest WTP value is in Semarang City and the lowest WTP value is in Yogyakarta City. Based on the results of the regression, the determinants that influence the value of WTP differ in each city, but income is a significant determinant in all cities. The value of willingness to pay chrysanthemum Pasopati cultivar can be used as a reference to set the selling price of chrysanthemum flowers. Chrysanthemum such as Pasopati cultivar in Indonesia, needs to be developed more by looking at the willingness of consumers to pay.